Pengaruh Harga, Kualitas Produk Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan(Studi Kasus Pelanggan Wardah di Universitas Muhammadiyah Surakarta) - Minawati, Azria Rahma, Drs. Sri Padmantyo., M.B.A (2017)
shown on the level of significance with regression value of 0.289.The implications of this study is that the vast majority of users would consider cosmetic Wardah price, product quality and service quality of Wardah to gain the loyalty of customers.Increasing number of cosmetics businesses in the modern period led to increasingly fierce competition. Thus the company is expected to make the right business strategy in order not to lose to competitors, so that customers will be satisfied and can create customer loyalty. The purpose of this study was to describe the effect of price, product quality and service quality to increase customer loyalty Wardah.This research was conducted by survey method using primary data obtained through questionnaires. The population in this study were students of Muhammadiyah University of Surakarta. The number of samples taken in this study as many as 100 people. Data were analyzed using the validity test, reliability test, classic assumption and regression, F test, T test, and test the coefficient of determination.The results of this study indicate that: (1) the effect on customer loyalty proved significant it is shown on the level of significance with regression value of 0,260. (2) the quality of the product effect on customer loyalty proved significant it is shown on the level of significance with regression value of 0.246. (3) The effect of service quality on customer loyalty proved significant it is